A perspectiva de uma antropologia behaviorista radical: cultura, variação, seleção e transmissão - Leugi, Guilherme Bergo (Universidade Federal de São Carlos, 2012)
Since the early writings on Radical Behaviorism there has been analysis of what is commonly known as the cultural level of variation and selection. Over the past 25 years, approximately, with growing interest by the scientific community on the culture topic, as well as conceptual developments regarding behavioral contingency analogies for the cultural determination, studies on Selection by Consequences model specifically for the culture have gained prominence. Skinner textually defines culture in many different ways throughout his work; nevertheless we believe it was possible to analyze them and theoretically propose an alternative understanding, based on most general principles of Radical Behaviorism with special attention to this theory determinism, regarding the functional relations established among environment and human actions. We understand that it is possible to comprehend the cultural system of determination of behavior as related to the environment which is historically and socially produced, not only referring to sets of behaviors repeated over generations. Cultural practices, as a proposition, would be redefined as parts of the behavioral environment (in this case, comprehended as reinforcing cultural practices). We also believe that it was possible to define a schematic model of determination based on the environmental and historical aspects, which is expected to be comprehensive in relation to culturally determined behavior (whether those behaviors produced in groups or those emitted alone, but which still are socially build). After these analyzes, we took a quick foray into Anthropology attempting to establish ways for the methodological inclusion of ethnography in the field of behavioral study of the culture. The current work is intended as an interpretative possibility and has not, of course, exhausted the subject matter or completely solved the problem of environmental determination on culture.
Keywords: Behaviorismo radical; Análise do comportamento; Seleção por consequências; Antropologia; Cultura; Determinismo Cultural.; Radical Behaviorism; Behavior Analysis; Selection by Consequences; Anthropology; Cultural Determinism.; CIENCIAS HUMANAS::FILOSOFIA